The Impact of Organizational Justice and Organizational Commitment on Turnover in the Employees of Allied Bank Peshawar Region - JUNAID ATHAR KHAN; SAIMA AFSHEEN; DR. SHAHID JAN; MUHAMMAD TARIQ (Journal of Business & Tourism, 2021)
The study is aimed to investigate the impact of organizational justice over the organizational commitment and turnover intention perceived by the employees regarding their jobs in the Allied Bank of Peshawar region. A total of 180 employees selected from different hierarchical levels of Bank responded to the questionnaires used for the evaluation of this study. The collected data is analysed with the help of the SPSS 22.0 version, which provided the descriptive statistical analysis that further reveal means of employee’s Organizational Justice with two dimension Distributive Justice and Procedural Justice of organizational commitment and turnover, i.e. reported as close to 3.0. Reliability of the study is considered as adequate because the Cronbach Alpha values were reported considerably above than the predetermined threshold of 0.70 for all the four variables of the study. Multiple regression analysis, factor analysis were also conducted to test the hypotheses of the study and as a result, it was evaluated that the two dimensions of the organizational justice, i.e. distributive and procedural have significant positive impact over the employee’s job commitment and reduction in turnover of employees to other banks or other organizations. The study will help the decision makers and especially the HR executives in obtaining some better understanding of the relationship of two variables with organizational justice, so that they can formulate certain suitable strategies for the employees and organization as a whole, which in turns lead to higher level of satisfaction among employees and improve their performance as a whole. A number of limitations of this study and recommendations for the future researchers are also discussed at the end of the study.